THE GENEALOGY OF FOUCALT AUTHORITY IN THE NEWS “PENAMPILAN CAPRES-CAWAPRES DIPOLES” OF KOMPAS DAILY - Dede Heri Pramono; Irma Silviani; Teti Sobari (IKIP Siliwangi, 2019)
This research is striving in the genealogy of Michael Foucalt in political discourse in the form of printed media. The chosen printed media is daily Kompas Friday edition, January 11th, 2019 page 2 with the news title “Penampilan Capres-Cawapres Dipoles”. This research background motivated by the phenomenon of political strategy in facing 2019 Presidential Election by using media as an instrument to gain electability. The research method which is used is qualitative approach with descriptive analysis techniques. The results of this study shows some conclusions; (1) The discourse production of Kompas daily is more likely creates reputation of Jokowi’s electability (2) Writing patterns was made by presenting Prabowo’s figure first which then outlines Jokowi's side and (3) To strengthen statements, which is coming from a third party from Jokowi's side and Prabowo's side was raised.